Technical performance test of drip irrigation system on cayenne pepper (Capsicum frutescens L.) cultivation in dry land of Slengen Village, North Lombok - Azhari, Anjar Pranggawan; Jufri, Afifah Farida; Nurrachman, Nurrachman; Jihadi, Amrul; Nufus, Novita Hidayatun (Universitas Muhammadiyah Mataram, 2023)
Cayenne pepper (Capsicum frutescens L.) is an agricultural commodity with a high economic value. Increasing cayenne pepper production in dry lands is hampered by limited water availability. Therefore, water use efficiency is required, one of which is the implementation of drip irrigation. This study aimed to test the performance of a drip irrigation system in the cayenne pepper farmland of Slengen Village, which is located in the lowlands with a dry climate (D4). Emitter discharge, emitter flow rate, and crop water requirements were used to determine the length of time the drip irrigation system was operational at each growth phase. The results show that the emitter discharge uniformity coefficient was 86.6% with a droplet distribution efficiency of 89.80%, which is included in the good category. This indicates that the drip irrigation system is suitable for irrigating plants evenly within the required water volume.